RESEARCH NITROGEN OXIDE EMISSIONS INTO THE AIR FROM BOILER UNITS FOR «-GENERATION-3" KHARKOV - and (Municipal economy of cities. Series: «Economy science», 2013)
A study of emissions of nitrogen oxides (NOx) in the air from the boilers at "3-generation" Kharkiv. Some measures to reduce NOx emissions below regulatory targets.